Safety of the concurrent use of gabapentin and carbamazepine at moderate therapeutic doses - Al-Mahmood, Sinan; Abdul Razak, Tariq; Che Abdullah, Shahrin Tarmizi; Nik Ahmad, Nik Nur Fatnoon; Mohamed, Abdul Hadi; Al-Ani, Imad Matloub Dally; Almola, Ehsan M.A. (College of Pharmacists of Buenos Aires Province, Argentina, 2017)
This study investigated the safety of concurrently administering different therapeutic doses of gabapentin (GBP) and carbamazepine (CBZ) on histopathological features and biochemical parameters of murine kidney and liver. Thirty five adult, female Sprague-Dawley rats were prepared and divided into five groups. Four drug regimens, using therapeutic doses calculated from human doses scaled by body surface area, were administered and any effects on kidney and liver biochemical parameters and histopathology were determined. Concurrent therapeutic administration of GBP and CBZ at high doses may produce adverse effects, but maintaining a moderate dose appears safe and may be appropriate, causing fewer side effects than high doses of a single drug or high dose combination therapy. Considera- tion should be given to the total drug load than to the individual doses of each medication. Combining GBP and CBZ in a specific ratio may enable the doses of each to be reduced, which may reduce adverse effects from combination treatments.